Creating a national breastfeeding and lactation policy for Canadian surgical residents - Rogowsky, Larissa; Ziolkowski, Natalia; Innis, Julia; Grant Buechner, Angela; Springall, Elena; Dengler, Jana (Canadian Medical Education Journal, 2024)
Background: Despite known benefits of breastfeeding and challenges medical trainees face lactating at work, research specific to Canadian surgical trainees is lacking. Our objectives were to examine existing breastfeeding and lactation policies, query experiences and opinions of surgical trainees and program directors, and propose a comprehensive policy for programs nation-wide. Methods: A multi-disciplinary team developed this two-part study. The scoping review used database and grey literature searches to find North American policies covering surgical residents. The survey study queried lactating Canadian surgical trainees and program directors about experiences and barriers, support provided, and interest in a breastfeeding and lactation policy. Results: Ten policies were found. None comprehensively addressed lactation space and supplies, break times, supports, and resident responsibilities. Among ten PD survey respondents: 60% were female, 70% had lactating trainees during their tenure, 40% discussed lactation accommodations, and all were willing to instate a policy. Among 24 trainees: 45% met breastfeeding goals, 74% stopped breastfeeding prematurely due to work barriers, and 88% had little workplace support. Almost all trainees (96%) wanted a policy. Conclusion: There is opportunity and appetite for a more comprehensive breastfeeding and lactation policy for Canadian surgical residents. Our policy highlights important areas where trainees can be better supported to meet breastfeeding goals.